HEWAN PELIHARAAN SEBAGAI HUMAN SUBSTITUTE DALAM KELUARGA JEPANG - Fajria Noviana (Diponegoro University, 2018)
Pets as human substitute in Japanese family. This study aims to describe the Japanese society's view of pets, especially in relation to the substitution of the position of family members, especially children, in a family. This is in line with the emergence of a phenomenon whereby the presence of children in the family has been replaced by pets, especially for those who choose not to have children or elderly citizens. The method used is analytical descriptive method and literature study. From the analysis results, it is known that the presence of pets in lieu of the presence of friends, family members, even biological child (human substitute) for some Japanese is a necessity. On the one hand, this can be seen as something positive because it raises human awareness in animals. But on the other hand, this can be interpreted as a decrease in the quantity and quality of interaction among human beings, which in the long term can affect a person's ability to show empathy to others.Keywords: pet; pet attachment; human substitute